Genetic diversity of HLA-DR and varion of asthma susceptibility; an overview of Asthma in Pregnancy - ACHMAD ARMAN SUBIJANTO (Biodiversitas Journal of Biological Diversity, 2008)
Asthma is the most common potentially serious medical condition to complicate pregnancy. To date, many attempts have been done to detect genetic loci contributing to asthma susceptibility. HLA-DR loci may play an important role in the pathophysiology of allergic inflammation by influencing specific IgE responses. Asthma affects almost 7 percent of women in their childbearing years. When women with asthma become pregnant, a third of the patients improve, one third worsen, and the last third remain unchanged. Asthma exacerbations are most likely to appear during the weeks 24 to 36 of gestation, with only occasional patients (10 percent or fewer) becoming symptomatic during labor and delivery. Uncontrolled asthma can cause serious complications for mother, including high bloodpressure, toxemia and premature delivery. For the baby, complications of uncontrolled asthma include increased risk of stillbirth, fetal growth retardation, premature birth, low birth weight and a low APGAR score at birth. The goal management of asthma during pregnancy is to achieve optimal therapy, maintaining controlled asthma and increased the mother and babyâ€™s quality of life. Most asthma medicationsare safe during pregnancy.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKeywords : Genetic diversity, asthma, pregnancy, managemen